(untitled) (Bulletin of criminological association of Ukraine, 2023)
The article is devoted to the development of a scientific understanding of the criminology of war as an integrative direction of criminological research and the practice of combating crime based on it. It aims at the epistemological specification and applied institutionalization of relevant intellectual and direct criminal preventive practices in order to reduce the frequency of reproduction of armed conflicts and the intensity of violations of fundamental human rights. occurring in their context. The author’s vision of the subject of criminology of war was formed, according to which 10 basic components were distinguished: war as a social-political, collective-psychological phenomenon; criminological phenomenology of war (criminal war and war crimes); determination of war crimes; the identity of the criminal; mechanism of individual criminal behavior; victims of war (criminological victimology of war); criminological phenomenology and determination of war-related criminal offenses; combating war crimes and war-related criminal offences; criminological provision of transitional justice; criminological phenomenology, determination and counteraction to global criminal and criminogenic effects of armed conflict. A description and explanation of each of them is provided.